The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s13063-023-07117-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-rich beet juice intake on cardiovascular performance in response to exercise in postmenopausal women with arterial hypertension: study protocol for a randomized controlled trial

Abstract: Background There is no evidence of the use of beetroot juice with a previously recommended dose of nitrate (NO3) (> 300 mg) on the cardiovascular performance during and recovery following exercise in postmenopausal women with systemic arterial hypertension (SAH). Methods We will investigate the effects of beetroot juice rich in NO3 acutely (800 mg) and during a week with daily doses (400 mg) on blood pressure, heart rate (HR), cardiac autonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Compared to men, women of reproductive age show a lower risk of hypertension; however, postmenopausal women present a higher risk of hypertension compared to age-matched male counterparts 6 , 7 . This elevated risk has been attributed to multiple factors ranging from estrogen and 17-β-estradiol deficiencies to vascular dysfunction 8 , 9 .…”
Section: Introductionmentioning
confidence: 92%
“…Compared to men, women of reproductive age show a lower risk of hypertension; however, postmenopausal women present a higher risk of hypertension compared to age-matched male counterparts 6 , 7 . This elevated risk has been attributed to multiple factors ranging from estrogen and 17-β-estradiol deficiencies to vascular dysfunction 8 , 9 .…”
Section: Introductionmentioning
confidence: 92%
“…Fresh beetroot fresh juice is most commonly used for nitrate supplementation, but it has a lower concentration compared to other beetroot products ( Table 2 ). Nevertheless, various studies have demonstrated a significant increase in nitrite levels (a marker of NO) in plasma after intake of beetroot juice [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Dietary Sources Of Nitratementioning
confidence: 99%
“…Moreover, different papers describe the fact that nitrate supplementation (including green leafy and root vegetables) may have an effect on cardiovascular health. They may help regulate blood pressure, limit a the progression of atherosclerosis, and improve myocardial contractility in healthy subjects and patients with cardiovascular diseases [ 8 , 10 , 23 , 36 , 37 , 39 ]. Figure 1 presents the beneficial action of nitric oxide (its regulatory and protective functions) in the cardiovascular system, together with the nitrate/nitrite/nitric oxide pathways.…”
Section: Nitric Oxide and Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations